On Strongly Regular Graphs With $m_2 = qm_3$ AND $m_3 = qm_2$ for $q = 5,6,7,8$ - Lepović, Mirko (Sarajevo Journal of Mathematics, 2020)
We say that a regular graph $G$ of order $n$ and degree $r\ge 1$ (which is not the complete graph) is strongly regular if there exist non-negative integers $τ$ and $θ$ such that $|S_i\cap S_j| = τ$ for any two adjacent vertices $i$ and $j$, and $|S_i\cap S_j| = θ$ for any two distinct non-adjacent vertices $i$ and $j$, where $S_k$ denotes the neighborhood of the vertex $k$. Let $λ_1 = r$, $λ_2$ and $λ_3$ be the distinct eigenvalues of a connected strongly regular graph. Let $m_1 = 1$, $m_2$ and $m_3$ denote the multiplicity of $r$, $λ_2$ and $λ_3$, respectively. We describe the parameters $n$, $r$, $τ$ and $θ$ for strongly regular graphs with $m_2 = qm_3$ and $m_3 = qm_2$ for $q = 5,6,7,8$.